2005
DOI: 10.1385/bter:103:2:109
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Content of Some Medicinal Plants Used in the Treatment of Diabetes Mellitus

Abstract: It is known that certain inorganic trace elements such as vanadium, zinc, chromium, copper, iron, potassium, sodium, and nickel play an important role in the maintenance of normoglycemia by activating the beta-cells of the pancreas. In the present study, the elemental composition in the leaves of four traditional medicinal plants (Murraya koenigii, Mentha piperitae, Ocimum sanctum, and Aegle marmelos) widely used in the treatment of diabetes-related metabolic disorders has been studied using atomic absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 18 publications
3
29
2
2
Order By: Relevance
“…[33] When OS extract is administered in streptozotocin diabetic rats mixed with vitamin it not only control glucose level [34] but also restore biochemical parameters and retinopathy [ Table 1]. [35,36] OS is used in diabetes related treatment of diabetes-related metabolic disorders, [37] and act both in hypoglycemic and hyperglycemic activity and restore glucose level. [38] OT (L.) showed the ability to inhibit glucosidase and α-amylase inhibitory property.…”
Section: Antidiabeticmentioning
confidence: 99%
“…[33] When OS extract is administered in streptozotocin diabetic rats mixed with vitamin it not only control glucose level [34] but also restore biochemical parameters and retinopathy [ Table 1]. [35,36] OS is used in diabetes related treatment of diabetes-related metabolic disorders, [37] and act both in hypoglycemic and hyperglycemic activity and restore glucose level. [38] OT (L.) showed the ability to inhibit glucosidase and α-amylase inhibitory property.…”
Section: Antidiabeticmentioning
confidence: 99%
“…Previous studies have shown that administration/intake of micronutrients are effective preventive and treatment measures for both type I and type II DM and common associated complications. Narendhirakannan et al, [52] reported the roles of inorganic trace elements present in four traditional medicinal plants (Murraya koenigii, Mentha piperitae, Ocimum sanctum, and Aegle marmelos) used in the treatment of DM. Also, Rajasekaran et al, [53] noted that inorganic elements like vanadium, zinc, sodium, potassium, calcium, copper, manganese, and traces of chromium zinc and chromium are required to correct glucometabolic disorders associated with DM.…”
Section: Discussionmentioning
confidence: 99%
“…From the outcomes, it was clear that a notable antinociceptive activity in the hotplate test and writhing response, which is similar to that of the standard. Studies show that different flavonoids, for example, luteolin, rutin, hesperidin, quercetin, and bioflavonoids produced substantial antinociceptive and anti-inflammatory activities [31]. A couple of reports on tannins as anti-inflammatory activities and antinociceptive properties.…”
Section: As An Anti-inflammatory Agentmentioning
confidence: 99%